2023
DOI: 10.60084/hjas.v1i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Size Distribution of Silver Nanoparticles Biofabricated Using Calotropis gigantea from Geothermal Zone

Pati Kemala,
Khairan Khairan,
Muliadi Ramli
et al.

Abstract: This research aims to synthesize silver nanoparticles (AgNPs) using an aqueous leaf extract of Calotropis gigantea obtained from the geothermal manifestation Ie Seu-Um, Aceh Besar, Aceh Province, Indonesia. The C. gigantea leaf extract was mixed with AgNO3 solutions at concentrations of 2, 5, and 9 mM, respectively. The mixture was stirred at 80 rpm by a magnetic stirrer for 48 hours in the dark. The change in solution color indicated the reduction of Ag+ to Ag0. The resulting AgNPs synthesized using C. gigant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The study of ants and their evolutionary links poses an interesting challenge due to their extensive diversity and ecological adaptations. To tackle this complexity, researchers have turned to mitochondrial DNA as a valuable tool [27,29,41,44,[50][51][52].…”
Section: Genetic Diversity and Phylogenetic Relationshipsmentioning
confidence: 99%
“…The study of ants and their evolutionary links poses an interesting challenge due to their extensive diversity and ecological adaptations. To tackle this complexity, researchers have turned to mitochondrial DNA as a valuable tool [27,29,41,44,[50][51][52].…”
Section: Genetic Diversity and Phylogenetic Relationshipsmentioning
confidence: 99%
“…These changes disrupt cell homeostasis, ultimately resulting in the destruction of microbial cells [22]. Various plants have been reported for the synthesis of AgNPs, including Picea abies [23], Zingiber officinale [24], Nigella sativa [24], Plumbago auriculata [25], Hypericum perforatum [26], Syzigyum cymosum [27], Lippia abyssinica [28], Zizyphus mauritiana [29] and Calotropis gigantea [30][31][32][33]. A recent study has shown that coating AgNPs synthesized with water hyacinth (Lablab purpureus) seed extract using patchouli oil (PO) enhances its antibacterial activity against E. coli [34].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental conditions resulting from hydrothermal alteration around the Ie Seu-um manifestation will impact the biosynthetic pathway of secondary metabolites in these plants. Numerous studies have demonstrated that many secondary metabolites play a role in the plant's adaptation system to its surroundings and exhibit antimicrobial activity [7][8][9].…”
Section: Introductionmentioning
confidence: 99%